PENERAPAN METODE IMAGE STREAMING PADA PEMBELAJARAN MENULIS PUISI SISWA KELAS X SMA NEGERI 2 PLAKAT TINGGI - Helsi Opiyeni; Dessy Wardiah; Liza Murniviyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effectiveness of the image streaming method in improving the poetry writing skills of tenth-grade students at SMA Negeri 2 Plakat Tinggi. The research used a quantitative approach with a Post-test Only Control Group Design. The population consisted of 213 students, with 72 students selected as samples, divided into an experimental group (X.1) and a control group (X.2). Data were collected through written tests assessing theme consistency, imagination, diction, figurative language, and concrete words. The results showed that the experimental group achieved a mean score of 85.22, significantly higher than the control group's mean of 69.67. Statistical analysis using the Independent-Samples T-Test yielded a tcount of 18.84, which exceeds the ttable value. Therefore, the null hypothesis (H0) was rejected, and the alternative hypothesis (Ha) was accepted. The findings conclude that the image streaming method significantly enhances students' creative expression and cognitive imagination in poetry writing compared to conventional methods.